WHEN INFERTILITY UNVEILS UNIFYING DIAGNOSIS: AN INSIGHT TO THE DISEASE - Ismail, Ilham; Jasmiad, Nurbadriah; See, Chee Keong; Shudim, Saiful Shahrizal (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Infertility involves investigation for primary or secondary causes. The presence of hypergonadotropic hypogonadism signifies premature ovarian failure (POF). When POF is accompanied by other endocrinopathies, a suspicion of underlying autoimmunity is possible. Autoimmune Polyglandular Syndrome (APS) is one of the rarer polyendocrinopathies that have multiple subtypes and clinical manifestations, including POF. We present a patient with a five-year history of diabetes and Graves’ disease (in remission) who came to the fertility clinic due to secondary amenorrhea. CASE A 36-year-old female with a background history of diabetes and Graves’ disease since 2018 presented to the gynaecology team in 2021 with primary infertility. Her diabetes was diagnosed as she presented with osmotic symptoms and was then treated accordingly with a combination of insulin and oral glucose-lowering medicine by a primary care physician. The diagnosis of Graves’ disease was made by the presence of typical thyrotoxic symptoms and a positive Anti-Thyroid Peroxidase Antibody (TPO). She was prescribed carbimazole and achieved remission after one year. With regard to primary infertility, she experienced oligomenorrhea, which then progressed to amenorrhea within two years. Her serial Follicle-Stimulating Hormone (FSH) and Luteinizing Hormone (LH) levels were noted to be in the menopausal range, while her progesterone was indicative of anovulation. She was then prepared for in-vitro fertilization (IVF). Suspicion of APS arose when she was admitted for diabetic ketoacidosis. The diabetes autoantibody panel was significantly positive – Anti-Islet Cells (ICA) and Anti-Glutamic Acid Decarboxylase (GAD); hence, a diagnosis of APS was made. CONCLUSION Manifestations of APS vary and, most of the time, will present multiple endocrine dysfunctions within a period of time. Diagnosis and management are clinically challenging. Therefore, it may be practical to screen for other autoimmune disorders in such patients periodically.